Disturbance Is an Important Driver of Clonal Richness in Tropical Seagrasses - McMahon, Kathryn M.; Evans, Richard D.; van Dijk, Kor-jent; Hernawan, Udhi; Kendrick, Gary A.; Lavery, Paul S.; Lowe, Ryan; Puotinen, Marji; Waycott, Michelle (Frontiers in Plant Science, 2017)
Clonality is common in many aquatic plant species, including seagrasses, where populations are maintained through a combination of asexual and sexual reproduction. One common measure used to describe the clonal structure of populations is clonal richness. Clonal richness is strongly dependent on the biological characteristics of the species, and how these interact with the environment but can also reflect evolutionary scale processes especially at the edge of species ranges. However, little is known about the spatial patterns and drivers of clonal richness in tropical seagrasses. This study assessed the spatial patterns of clonal richness in meadows of three tropical seagrass species, Thalassia hemprichii, Halodule uninervis and Halophila ovalis, spanning a range of life-history strategies and spatial scales (2.5 – 4 711 km) in Indonesia and NW Australia. We further investigated the drivers of clonal richness using general additive mixed models for two of the species, H. uninervis and H. ovalis, over 8° latitude. No significant patterns were observed in clonal richness with latitude, yet disturbance combined with sea surface temperature strongly predicted spatial patterns of clonal richness. Sites with a high probability of cyclone disturbance had low clonal richness, whereas an intermediate probability of cyclone disturbance and the presence of dugong grazing combined with higher sea surface temperatures resulted in higher levels of clonal richness. We propose potential mechanisms for these patterns related to the recruitment and mortality rates of individuals as well as reproductive effort. Under a changing climate, increased severity of tropical cyclones and the decline in populations of mega-grazers have the potential to reduce clonal richness leading to less genetically diverse populations